PROFIL PENGKAJIAN RESEP RACIKAN PEDIATRI PASIEN RAWAT JALAN DI RUMAH SAKIT MUJAISYAH KOTA PALOPO - Syamsuddin, Puja; Nurlina, Nurlina; Purnamasari M., Vina (Fakultas Farmasi UMI, 2024)
Prescription review is an activity in pharmaceutical services that is used to minimize errors in drug prescribing. This study aims to assess the prescription of pediatric concoctions at Mujaisyah Hospital, Palopo City. This research method is descriptive non-experimental with retrospective data collection. The population in this study were all incoming prescriptions in the pharmaceutical installation of Mujaisyah Hospital, Palopo City for the period January - June 2023 which met the inclusion criteria, namely 115 prescription sheets. The results showed the percentage of completeness of administrative aspects, namely the patient's name and age 100%, gender 0%, weight 73.04%, height 0%, name, address, initials, and doctor's license number 98.26%, prescription date 99.13%, prescription origin unit 98.26%. The suitability of pharmaceutical aspects, namely drug name, dosage form, drug dose, drug amount, rules and method of use 100%, dosage strength 10.43%, incompatibility 29.56%, hygroscopic stable drugs 52.79% and photolysis 47.21%. The suitability of clinical aspects, namely the accuracy of indications and the accuracy of time of use 100%, the accuracy of dosage 86.48%, and drug interactions 50.44%. From the results of this study, it can be concluded that the prescription at Mujaisyah Hospital, Palopo City has not fully complied with Permenkes RI No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals